2015
DOI: 10.1016/j.rbmo.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

How to define, diagnose and treat poor responders? Responses from a worldwide survey of IVF clinics

Abstract: Poor responders represent a significant percentage of couples treated in IVF units (10-24%), but the standard definition of poor responders remains uncertain and consequently optimal treatment options remain subjective and not evidence-based. In an attempt to provide uniformity on the definition, diagnosis and treatment of poor responders, a worldwide survey was conducted asking IVF professionals a set of questions on this complex topic. The survey was posted on www.IVF-worldwide.com, the largest and most comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 99 publications
1
63
0
Order By: Relevance
“…Surveys such as that conducted by Patrizio et al . found that the best stimulation protocols for poor ovarian responders were the GnRH antagonist protocol (52%), the short GnRH agonist flare‐up (20%), and microdose (15%) protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys such as that conducted by Patrizio et al . found that the best stimulation protocols for poor ovarian responders were the GnRH antagonist protocol (52%), the short GnRH agonist flare‐up (20%), and microdose (15%) protocols.…”
Section: Introductionmentioning
confidence: 99%
“…8 Another study showed FSH level of 6.5-15 mIU/mL as poor responders. 9 Basal FSH level performed better as a sole prognosticator for treatment failure, but the high cut off level necessary to reach sufficient prognostic power inevitably reduces the number of patients that may benefit from the test. Basal FSH is a limited value in the prediction of pregnancy rate after IVF and should only be applied if clear consequences, therefore another predictive factor is needed to predict fertility success.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with poor ovarian response (POR) present a major challenge in IVF, as they are not likely to obtain an optimal number of oocytes after OS, and thus are less likely to conceive and, moreover, will have a higher risk of cycle cancellation. The estimated prevalence of POR ranges from 6% to 35% [3,4]. This wide range is caused by the initial lack of consensus when defining POR.…”
Section: Introductionmentioning
confidence: 99%